2009
DOI: 10.1002/ijc.24115
|View full text |Cite
|
Sign up to set email alerts
|

HAI‐2 is epigenetically downregulated in human hepatocellular carcinoma, and its Kunitz domain type 1 is critical for anti‐invasive functions

Abstract: Pharmacological demethylation-based gene expression profile analysis is a useful tool to identify epigenetically silenced tumour suppressor genes. HGF activator inhibitor 2 (HAI-2), a serine protease inhibitor, has been identified as one of the candidate tumour suppressor genes in human hepatocellular carcinoma (HCC) with this technique. In this study, we aimed to characterise the epigenetic status and tumour suppressive function of HAI-2 in HCC. We validated that HAI-2 expression was either absent or low in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Two of these, GSTP1 [13], [40] and SPINT2 [41], [42] were previously reported tumor suppressor genes which were hypermethylated in tumors with corresponding down-regulated gene expression, while the other 2 (CYB5R2 and SH3YL1) represent potential novel tumor suppressor genes. Quantitative real-time PCR and pyrosequencing successfully validated all four genes (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Two of these, GSTP1 [13], [40] and SPINT2 [41], [42] were previously reported tumor suppressor genes which were hypermethylated in tumors with corresponding down-regulated gene expression, while the other 2 (CYB5R2 and SH3YL1) represent potential novel tumor suppressor genes. Quantitative real-time PCR and pyrosequencing successfully validated all four genes (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies dealing with the methylation profile in HCCs did not tackle the role of HCV in epigenetic changes during hepatocarcinogenesis. Some had less than five HCV-induced HCC cases (Deng et al, 2010;Ammerpohl et al, 2012), while others lacked normal controls and only included adjacent noncancerous liver tissues (Fukai et al, 2003;Su et al, 2008;Hernandez-Vargas et al, 2010;Shen et al, 2012;Shin et al, 2010;Shitani et al, 2012) as well as HCC cell lines (Tung et al, 2009). Moribe et al (2009) reported that the SPINT2/HAI-2 gene promoter was highly unmethylated in the normal liver from healthy individuals and in the liver from HCV carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of SPINT2/HAI-2 promoter hypermethylation on its gene expression was proved by Tung et al (2009), using bisulfite sequencing and MSP; they found that most HCC cases had underexpression of the SPINT2/ HAI-2 gene when the promoter region was hypermethylated. It is noteworthy to mention that such a low expression noted in HCC can be hardly explained by somatic mutations of SPINT2/HAI-2, which are quite rare (Morris et al, 2005), thus favoring the role of epigenetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations